Assessing the Change in Social Status of Scheduled Castes: A Case Study of Rural Haryana (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Haryana is a historically dominated state by rigid agrarian caste hierarchies and traditional social structures. The present paper tries to examines the shifting socio-economic and political landscape of Scheduled Castes (SCs) in rural Haryana by applying a mixed-method approach on the basis of secondary data with empirical knowledge collected through field observations across the selected districts in the state. The study also tries to access the primary drivers of social mobility and persistent barriers of true equality. The findings of the study reveals that the scheduled caste population in Haryana shows a notable transition in the past few decades. The findings also reveals that structural shifts in the rural economy-specifically the decline of traditional jajmani ties, infusion of mechanization in agriculture, and a subsequent migration toward urban areas have significantly reduced traditional forms of economic dependency on dominant landowning castes. Furthermore, state-led affirmative action, coupled with rising literacy rates and digital connectivity, has fostered a heightened sense of political consciousness and legal awareness especially among the youth of schedule castes. The study highlights that occupational mobility and political reservation have enabled institutional representation while substantive social integration remains contested. The ritual hierarchies, residential segregation, and subtle forms of everyday discrimination persist in scheduled caste residency pockets. The backlash against assertive schedule caste identities often manifests in localized conflicts, revealing deep-seated structural anxieties among dominant agrarian communities. The study shows that traditional caste-class nexus is weakening economically while deep-rooted social prejudices continue to adapt in modern contexts.